Genealogy on Policies and Strategies of Physical Education for Elementary Schools in Indonesia - Sumarjono Sumarjono; Soni Nopembri; Hari Yuliarto (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This paper delves into an examination of policies and strategies for physical education in elementary schools, with a specific focus on assessing their effectiveness and sustainability to enhance the overall quality of physical education. Employing a qualitative approach that involves a comprehensive review of relevant literature, the study aims to scrutinize and evaluate the impact of these policies and strategies. The findings highlight crucial elements essential for effective physical education, such as the development of a well-rounded curriculum, accurate assessment methods, continuous teacher training, institutional and governmental support, integration of modern technology, fostering community partnerships, and active involvement of parents. The conclusions drawn from this research underscore the critical importance of implementing robust policies and strategies to address the existing challenges in elementary school physical education. Furthermore, the study emphasizes the potential for significant improvements in the effectiveness and sustainability of physical education through the adoption and implementation of these measures, ultimately paving the way for a more holistic and beneficial educational experience for students.